Secondary Metabolite Profile of Essential Oils of Kaffir Lime, Kalamansi, and Lime Fruit Peels from South Sumatra - Astri Indah Lestari; Salni Salni; Laila Hanum (Universitas Muhammadiyah Enrekang, 2024)
This study aims to determine the secondary metabolite content of the essential oils of kaffir lime, kalamansi and lime peels from South Sumatra. This research consisted of several stages, namely the stage of identifying kaffir lime, calamansi and lime plants, the stage of preparing tools and materials, the stage of distillation of the essential oils of kaffir lime, calamansi and lime peels and the stage of identifying the chemical components of essential oils using the GC-MS method. Based on research, it can be concluded that the main essential oil content of kaffir lime peel, calamansi and lime from South Sumatra are citronellal (24.55%), limonene (97.12%) and limonene (35.24%) respectively.